2021
DOI: 10.1016/j.adolescence.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exposure to violence on adolescents’ physical aggression: The protective influence of peers

Abstract: Introduction: This study examined the degree to which peers can serve as a protective factor to mitigate the negative effects of exposure to violence (i.e., victimization, witnessing violence) on adolescents' physical aggression. Four speciic dimensions of peer inluence were examinedfriends' support for nonviolence, friends' support for ighting, peer pressure for ighting, and friends' delinquent behavior. Methods: Analyses were conducted on four waves of data collected every 3 months (i.e., fall, winter, sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The role of social-ecological and individual protective factors may differ across contexts (Ungar, 2015). One study found that peer variables, particularly low levels of friends' delinquent behavior and peer pressure for fighting and high levels of friends' support for nonviolence, attenuated the relation between victimization and subsequent physical aggression (Coleman & Farrell, 2021). However, findings differed by gender and season of year, highlighting the importance of context, time, and gender when identifying factors that might promote resilience in youth exposed to violence.…”
Section: Moderating Role Of Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of social-ecological and individual protective factors may differ across contexts (Ungar, 2015). One study found that peer variables, particularly low levels of friends' delinquent behavior and peer pressure for fighting and high levels of friends' support for nonviolence, attenuated the relation between victimization and subsequent physical aggression (Coleman & Farrell, 2021). However, findings differed by gender and season of year, highlighting the importance of context, time, and gender when identifying factors that might promote resilience in youth exposed to violence.…”
Section: Moderating Role Of Adultsmentioning
confidence: 99%
“…This manuscript was based on data from an 8-year project that collected longitudinal data within each school year from 10 cohorts of students attending three urban middle schools. Several prior manuscripts based on these data have examined bidirectional relations between exposure to violence and physical aggression (Farrell, Thompson, Curran, & Sullivan, 2020), peer factors as mediators (Farrell, Pittman, O'Connor, & Sullivan, 2022), and moderators (Coleman & Farrell, 2021) of relations between violence exposure and physical aggression, and beliefs as mediators of relations between violence exposure and physical aggression (Farrell, Pittman, Bettencourt, et al, 2022).…”
Section: Ac K Now L E D G M E N T Smentioning
confidence: 99%
“…Belonging to gangs might provide strength to those students who need it, and school can be a place to show off their superiority by engaging in physical fights and bullying “opponents”. The risk of bullying and fights could be lowered by preventive measures and actions that favor positive peer influence and peer support during adolescence [ 15 , 16 ] and in school settings in particular [ 14 , 17 ]. Differences in the prevalence of bullying and its types along with better understanding of such phenomena in school-age children can have an impact on various authorities, including schools, parents or legal guardians, and health care workers, to propose and create preventive measures and interventions that would have a positive response in reducing unfavorable behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to community violence has been related to a range of negative outcomes among adolescents, such as mental health problems 6 , depression 7 , anxiety 8 , post-traumatic stress disorder 9 , aggression 10 and delinquency 11 . Studies using neuroimaging have shown an association between ECV and reduced gray matter volume and lower IQ 12 , and ECV in early adolescence as a predictor of lower hippocampal and amygdala volume in late adolescence, which may imply impairments in learning, memory, and emotion processing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A exposição à violência comunitária tem sido relacionada a uma gama de desfechos negativos entre os adolescentes, como problemas de saúde mental 6 , depressão 7 , ansiedade 8 , transtorno de estresse pós-traumático 9 , agressão 10 e delinquência 11 . Estudos utilizando neuroimagem mostraram associação entre EVC e redução de volume da substância cinzenta e menor QI 12 e EVC no início da adolescência como fator preditor de menor volume do hipocampo e da amígdala ao final da adolescência, o que pode implicar em prejuízos na aprendizagem, memória e no processamento de emoções 13 .…”
Section: Introductionunclassified